Zebrafish churchill regulates developmental gene expression and cell migration. Issue 6 (29th March 2013) - Taibi, Andrew; Mandavawala, Kunal P.; Noel, Justine; Okoye, Ejike V.; Milano, Carolyn R.; Martin, Benjamin L.; Sirotkin, Howard I.
<x xml:space="preserve">Abstract</x> Background: Regulation of developmental signaling pathways is essential for embryogenesis. The small putative zinc finger protein, Churchill (ChCh) has been implicated in modulation of both TGF‐β and FGF signaling. Results: We used zinc finger nuclease (ZFN) mediated gene targeting to disrupt the zebrafish chch locus and generate the first chch mutations. Three induced lesions produce frameshift mutations that truncate the protein in the third of five β‐strands that comprise the protein. Surprisingly, zygotic and maternal zygotic chch mutants are viable. Mutants have elevated expression of mesodermal markers, but progress normally through early development. chch mutants are sensitive to exogenous Nodal. However, neither misregulation of FGF targets nor sensitivity to exogenous FGF was detected. Finally, chch mutant cells were found to undergo inappropriate migration in cell transplant assays. Conclusions: Together, these results suggest that chch is not essential for survival, but functions to modulate early mesendodermal gene expression and limit cell migration. Developmental Dynamics 242:614–621, 2013. © 2013 Wiley Periodicals, Inc.†